THE RUSSIAN VERSION OF THE CHILDHOOD HEALTH ASSESSMENT QUESTIONNAIRES(CHAQ) AND THE CHILD HEALTH QUESTIONNAIRES (CAQ) - N N Kuzmina; J P Nikishina; A V Shaikov; N Ruperto; T A Shelepina; S O Salugina (Научно-практическая ревматология)
We report herein the results of the cross-cultural adaptation and validation into the Russian language of the parent’s version of two health related quality of life instruments. The Childhood Health Assessment Questionnaire (CHAQ) is a disease specific health instrument that measures functional ability in daily living activities in children with juvenile chronic arthritis (JCA). The Child Health Questionnaire (CHQ) is a generic health instrument designed to capture the physical and psychosocial well-being of children independently from the underlying disease. The Russian CHAQ-CHQ were fully validated with 3 forward and 3 backward translations. A total of 146 subjects were enrolled: 86 patients with JCA (23% systemic onset, 39% polyarticular onset, 15% extended oligoarlicular subtype, and 23% persistent oligoarticular subtype) and 60 healthy children. The CHAQ clinically discriminated between healthy subjects and JCA patients, with the systemic, polyarticular and extended oligoarticular subtypes having a higher degree of disability, pain, and a lower overall wellbeing when compared to their healthy peers. Also the CHQ clinically discriminated between healthy subjects and JCA patients, with the systemic onset, polyarticular onset and extended oligoarticular subtypes having a lower physical and psychosocial well-being when compared to their healthy peers. In conclusion the Russian version of the CHAQ-CHQ is a reliable, and valid tool for the functional, physical and psychosocial assessment of children with JCA.